Pelaksanaan Surveilans Kesehatan dan Kesiapsiagaan Masyarakat Pasca Erupsi Merapi 2010 Pada Pelaksanaan Desa Siaga di Desa Talun Klaten - Rio Rialdi; Sunarto Sunarto (Universitas Muhammadiyah Surakarta, 2013)
Indonesia is one country that is classified as vulnerable to natural disasters. Merapi eruption isone of the natural disasters that have an impact on public health. Standby village is an important pillarin handling disasters, since people usually are not prepared if there is a sudden disaster. The purposeof the study was to determine the application program of public health surveillance and preparednessafter the eruption of Merapi of 2010 in the implementation of standby village in Talun Village, KemalangSub-district, Klaten District Central Java. The research was descriptive using study case with qualitativeanalysis. The subject of the study was performers implementing public health surveillance program.The object of the study was the social situation in performing program. Informant was determinedbypurposive and snowball effect. Datawere collected by non participativeobservation, interview,documentation,focus discussion group (FGD), and triangulation. Judging from some indicators, the implementationof standby village had been running well. The performing of public surveillance program hasnotbeen running properly due to lack of socialization of the health center. The community disasterpreparednessprogram was good enough. However,it should be improved to preparednessupon healthemergencies.Standby village program and community preparedness is good enough, however it is notfollowedby a good surveillance based on community.